Using policy scenarios to assess challenges and opportunities for reaching restoration targets in Brazil’s Atlantic Forest - Shennan-Farpón, Y; Soterroni, AC; Scarabello, M; Visconti, P (IOP Publishing, 2024)
Brazil’s Atlantic Forest is a global restoration hotspot. Most of the remaining forest areas are degraded and separated by large cities, and agricultural lands essential for national food security. Brazil’s restoration agenda is defined by multiple national and global restoration targets and policies, including Brazil’s Native Vegetation Protection Law (No. 12,651/2012) also known as the Forest Code, which sets minimum levels of native vegetation to be maintained or restored in rural properties. In this study we simulate the impacts of alternative restoration policies addressing targets for Brazil, and explore their impacts on selected terrestrial species and agricultural development potential in the Atlantic Forest biome. Our results show several policy options could result in different restoration amounts and spatial distributions being implemented between 2020 and 2050, but trade-offs between agriculture, biodiversity and rural livelihoods differ. Compared to the baseline scenario (implementation of the Forest Code), a scenario which focuses restoration on small farms (not mandated to undergo restoration under the current legislation) could increase forest area by 6.7 Mha across the biome (139% more than with the Forest Code), while a scenario which maximizes biodiversity gains could lead to an additional 3.9 Mha by 2050 (81% more compared to the Forest Code). We find that our restoration scenarios still allow cropland expansion and an increase in cattle herd, while pasturelands decrease. There are relatively small agricultural production losses under the alternative restoration scenarios when compared to the baseline (up to 14.4%), meaning that cattle ranching intensification is critical to enable large-scale restoration to co-exist with agricultural production. Our scenarios suggest that ambitious restoration targets in the Atlantic Forest biome (up to 15.5 Mha, consistent with existing regional initiatives) could be feasible with necessary improvements in pasture yield and a focus on scaling up support and developing restoration policies for smallholder farmers.